Tutor Readiness in the Implementation of E-PKBM in the Equivalency Education Program - Saleha, Najwa Ayu; Shofwan, Imam (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
Non-formal education in Indonesia, particularly in the context of equivalency education, faces numerous challenges in introducing innovation to the learning system. This study aims to describe the readiness of tutors in implementing E-PKBM by using a qualitative approach and descriptive method. Data was collected through observation, interviews, and documentation, and their validity was tested through source triangulation and technique triangulation. Data analysis included data collection, data reduction, data presentation, and conclusion drawing. The results describe (1) tutors show professional confidence in implementing the system, although they still need support and further training to handle complex questions. (2) Comprehensive institutional support, including training, appreciation of achievements, and constructive communication, is crucial. (3) Tutors need to develop competence in using the system to optimize the learning process. The implications of this study emphasize the need for continuous training programs and the development of self-learning skills. This study concludes that tutor readiness makes a significant contribution to the success of E-PKBM, and these findings make a valuable contribution to the development of tutor training programs in PKBM.